God’s not dead 1 - Open Education Model of religious education in the world of mixed values - Zamkowska, Iwona (Journal of Education Culture and Society, 2020)
Aim. The aim of the research is to explore the functionality of the Open Education Model of religious education for the “form[ation of] an internal moral compass,” as Steven Hitlin and Jane Allyn Piliavin (2004) describe the modern understanding of values. In other words, the author will attempt to explore first what the model has to offer in terms of equipping students with the necessary skills so that they will successfully navigate through the conflict of values, and second the potential application and limitations of the model. Methods. The exploration is based on a 2014 production by Pure Flix Entertainment, the first movie in the God’s not Dead series. The author will consider two educational cases presented in the movie using a close reading method. Results. The study seems to prove that that the God’s not Dead movie accurately portrays the conflict of values experienced by young adults in present-day America. It also appears to consistently promote the Open Education Model as a type of religious education that provides considerable assistance to the learners in retaining their beliefs in the world of mixed values, especially in the time of crisis. The model appears to lend sound conceptual framework missing in other models, but its full application is time and effort consuming and fails to provide more comprehensive approach to religious diversity. Conclusion. The Open Education Method of religious instruction in the environment dominated by a multicultural approach, seems to offer valuable concepts that may facilitate educational process proposed by other models and thus deserves more thorough consideration in academic research.